High-temperature steady-state experiments on G550 cold-formed steel during heating and cooling stages. (June 2020) - Chen, Wei; Liu, Kun; Ye, Jihong; Jiang, Jian; Xu, Changzheng; Jin, Lei; Zhang, Meng
Abstract: Steel structures usually experience heating and cooling stages during a compartment fire. Most previous investigations on the high-temperature material properties of cold-formed steel (CFS) focused on the heating stage of steel, corresponding to the growth and fully developed phases of a compartment fire. The influence of the cooling stage of steel, which corresponds to the decay phase of a compartment fire, has not been properly considered. This study conducted 88 steady-state tests on G550 CFS at elevated temperatures and investigated the material properties during the heating and cooling stages. The results show that the prediction of the time-dependent load-bearing capacity of CFS structures under compartment fires might become non-conservative if the material properties of the G550 CFS during the cooling stage are replaced with those during the heating stage. For instance, when the tensile temperature is less than 500 °C and the peak temperature is greater than or equal to 600 °C, the yield strength reduction factors of G550 CFS during the cooling stage are significantly lower than those during the heating stage under the same tensile temperature. In addition, the distribution of the yield strength (ultimate strength) reduction factors of G550 CFS during the cooling stage is affected by the peak and tensile temperatures and displays two branches. The difference in the reduction factors between the two branches is significant under the same tensile temperature and different peak temperatures. Finally, unified equations for the material property reduction factors and stress–strain curves are proposed and can provide a reasonable prediction of the material properties of G550 CFS under full-range compartment fires. Highlights: Steady-state tests of CFS were conducted during heating and cooling stages. The difference in the test results during heating and cooling stages is significant. The distribution of yield strength curves during the cooling stage displays two branches. The prediction of the bearing capacity of CFS structures in fires might become non-conservative. Expressions are provided for the material properties of G550 CFS under full-range fire.